2019
DOI: 10.1007/s10869-019-09619-w
|View full text |Cite
|
Sign up to set email alerts
|

Identity, Importance, and Their Roles in How Corporate Social Responsibility Affects Workplace Attitudes and Behavior

Abstract: This paper contributes to growing research exploring employee attitudinal and behavioral reactions to organizational corporate social responsibility initiatives focused on environmental and social responsibility and sustainability. Drawing on social identity theory, we develop and test a moderated-mediation model where employees' organizational identification mediates the relationship between their perceptions of organizational CSR initiatives and their work engagement and organizational citizenship behaviors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 51 publications
2
32
0
2
Order By: Relevance
“…In their study, they also did not find a direct relationship between CSR and OCB, and in their study, the relationship between CSR and OCB was only revealed when other aspects were considered. Other researchers also came to this conclusion: Identification transmitted the relationship between CSR and OCB only when the employees' importance of and values toward CSR as a moderating factor was taken into account (van Dick et al, 2019). Although our findings, specifically the tests of our hypothesis, provide evidence for organizational identification as an explaining mechanism for the effects of CSR on employees, the low variance explanation is attracting attention: CSR only explains 4% of the variance while predicting identification.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In their study, they also did not find a direct relationship between CSR and OCB, and in their study, the relationship between CSR and OCB was only revealed when other aspects were considered. Other researchers also came to this conclusion: Identification transmitted the relationship between CSR and OCB only when the employees' importance of and values toward CSR as a moderating factor was taken into account (van Dick et al, 2019). Although our findings, specifically the tests of our hypothesis, provide evidence for organizational identification as an explaining mechanism for the effects of CSR on employees, the low variance explanation is attracting attention: CSR only explains 4% of the variance while predicting identification.…”
Section: Discussionsupporting
confidence: 58%
“…Job satisfaction -a pleasurable or positive emotional state resulting from the appraisal of one's job or job experiences (Locke, 1976) -was also often investigated as an outcome of CSR, but to our knowledge only in cross-sectional research designs (Valentine and Fleischman, 2007;Shin et al, 2016). Job satisfaction depends on how employees evaluate their job situation (van Dick et al, 2004;Shin et al, 2016), which also includes the perception of CSR initiatives. A positive evaluation of CSR initiatives can increase job satisfaction.…”
Section: Csr and Its Relationship With Employee-related Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, mediation of organizational identification has been considered for the link between perceived CSR and employee loyalty, commitment, and job performance [23]. Employees tend to present favorable behaviors at the workplace when they strongly identify with their organization [3]. Firms' CSR initiatives enhance employees' perception of oneness with their organizations, and they tend to identify with their organizations to enhance their self-respect [24,25].…”
Section: Mediation Of Organizational Identification Between Csr and Ementioning
confidence: 99%
“…Numerous attempts have been made to investigate the ability of organizational CSR initiatives to positively affect the behaviors of its employees through the lens of social identity theory. These positive impacts include employees' positive perceptions towards their companies' CSR and employees' organizational citizenship behavior [1], job satisfaction [2] and organizational identification [3]. In addition, there has been a recommendation to consider employees while developing social sustainability measures [4] and dedication of], as well as increased focus on special issues involving micro-CSR from organization behavior and human resource management journals [5].…”
Section: Introductionmentioning
confidence: 99%